2002
DOI: 10.1002/etc.5620210705
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of compounds from bleached kraft mill recovery condensates associated with reduced levels of testosterone in mummichog (Fundulus heteroclitus)

Abstract: Previous studies have identified chemical recovery condensates as a primary source of hormonally active substances within a Canadian bleached kraft pulp mill. Although reverse osmosis treatment of condensates raises the exposure threshold that alters circulating levels of testosterone in mummichog (Fundulus heteroclitus), the responsible chemicals have not been characterized. In this study, a solid-phase extraction (SPE) method was developed to isolate chemical recovery condensate extractives for evaluation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 31 publications
1
26
1
Order By: Relevance
“…Future work focused on the SPE-2 fraction since it exhibited the greatest potential for depressing hormones in both sexes. A comparison study showed that condensates derived from both hardwood and softwood batch production runs at IPP had an equal potential to lower hormone levels (Hewitt et al 2002). In terms of identifying characteristics of the compounds involved, this evidence showed them to be organic, water soluble, and readily bioavailable to fi sh.…”
Section: Investigation Of Cause Approachmentioning
confidence: 98%
See 3 more Smart Citations
“…Future work focused on the SPE-2 fraction since it exhibited the greatest potential for depressing hormones in both sexes. A comparison study showed that condensates derived from both hardwood and softwood batch production runs at IPP had an equal potential to lower hormone levels (Hewitt et al 2002). In terms of identifying characteristics of the compounds involved, this evidence showed them to be organic, water soluble, and readily bioavailable to fi sh.…”
Section: Investigation Of Cause Approachmentioning
confidence: 98%
“…A solid-phase extraction (SPE) method was developed by Hewitt et al (2002) to isolate chemical recovery condensate extractives for the evaluation of their hormonal activity. In this work, hormone depressions in mummichog were used to direct SPE method development.…”
Section: Investigation Of Cause Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…Organic compounds in the wood itself are the most likely cause of reproductive suppression (Dube and MacLatchy 2001). Hewitt et al (2002) showed that compounds derived from both hardwoods and softwoods caused similar suppressive effects.…”
Section: Discussionmentioning
confidence: 97%